Peran Guru Dalam Melindungi Anak Dari Eksploitasi Dan Kekerasan Di Lingkungan Sekolah - Agus Jaenal (Departement of Mathematics Education, 2024)
The role of teachers in protecting children from exploitation and violence in the school environment is very important to create a safe atmosphere for students. The presence of responsive and caring teachers can prevent acts of violence and provide the emotional support that children need in the learning process. This research aims to evaluate the effectiveness of the protection provided by teachers and identify the challenges faced in this process. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews and document analysis. The research results show that teachers at SDIT Kasih Ibu have carried out their role well in supervising and communicating with students, but supervision outside the classroom still needs to be improved. Only 70% of teachers actively supervise students during recess and extracurricular activities, and 60% of teachers feel they have received insufficient training in handling cases of violence. Apart from that, only 50% of case reports receive clear follow-up from the school. The implications of this research indicate the need to increase training for teachers and strengthen reporting systems to create a safer school environment. It is hoped that this research can become a reference for policy makers in designing more effective and comprehensive student protection programs in the future.